Same‐Day Discharge After Catheter Ablation of Atrial Fibrillation in the United States - Amneet Sandhu; Li Qin; Karl Minges; Sarah Zimmerman; Ryan T. Borne; Vincenzo B. Polsinelli; P. Michael Ho; Jonathan C. Hsu; Sana M. Al‐Khatib; James V. Freeman; Steven M. Bradley; Sunil V. Rao; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Patients undergoing atrial fibrillation (AF) ablation have historically been hospitalized overnight or longer postprocedure. National rates of same‐day discharge (SDD) following AF ablation remain unknown. Methods and Results The NCDR (National Cardiovascular Data Registry) AF Ablation Registry was used to identify index procedures from January 1, 2016 to June 30, 2023. Patients were stratified by postprocedure disposition: (1) SDD, (2) overnight hospitalization (<1 day), or (3) >1 day hospitalization. Rates, clinical factors, and hospital‐level variation associated with SDD were analyzed. Among 139 391 patients who underwent AF ablation across 197 hospitals, 51 622 (37.0%) underwent SDD, 78 220 (56.1%) were hospitalized overnight, and 9549 (6.9%) for >1 day postprocedure. SDD rates increased from 0.99% in Q1 2016 to 62.3% in Q2 2023 (P<0.0001), surpassing overnight hospitalization in Q1 of 2021. The likelihood of SDD increased significantly over time (odds ratio [OR], 1.26 per quarter‐year [95% CI, 1.26–1.26]) with substantial variation across hospitals (median OR, 4.12 [95% CI, 3.48–4.79]). Those discharged the same day were less likely of Black race (OR, 0.71 [95% CI, 0.65–0.78]) and to have persistent AF (OR, 0.85 [95% CI, 0.82–0.88]) and cardiomyopathy (OR, 0.87 [95% CI, 0.84–0.91]). In total, major and overall complication rates were 0.70% and 2.13%, respectively. Major and overall complication rates were 0.03% and 0.19% for SDD and 0.24% and 0.98%, respectively, for overnight hospitalization. Conclusions Rates of SDD following AF ablation markedly increased over time, corresponding with onset of the COVID‐19 pandemic, with substantial hospital variation. SDD patients had fewer comorbid conditions and were less likely to have persistent AF. Postprocedural complication rates with SDD were low and comparable with patients hospitalized overnight.